PENGGUNAAN MEDIA FLASHCARD MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PENJUMLAHAN DI SDN KEDONDONG 1 TULANGAN - Nur Fika Indah Sari; Muhammad Yusron Maulana El-Yunusi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning at the elementary level is an important foundation in a child's development. In this process, students begin to learn various basic school subjects such as counting, especially in mathematics. Learning is a dynamic approach towards students, for educators and learning media. In this process, learners actively engage to build new knowledge and skills to achieve learning objectives in accordance with the planned guidelines. Learning means communicating effectively in one's environment. Creating enjoyable learning requires the use of learning media. This research aims to determine the effectiveness of using Flashcard media tools to improve the learning outcomes of second-grade students at SDN KEDONDONG 1 TULANGAN, particularly in addition mathematics. The research method that will be applied is qualitative, with a total of 14 students. By using these flashcards, it can reduce the level of boredom and tension among students during daily learning activities. Flashcards are an educational medium that is very engaging for students; with these flashcards, they can improve their memory, increase their vocabulary, and train their independence. Applying flashcard media for better learning abilities results in more satisfying learning outcomes compared to previous teaching methods. This allows for the appreciation that recognizing numbers, learning to count, and adding can use flashcard media to achieve improved student performance.